The use of geotechnology to determine areas with forestall potential: an approach about water availability - Santos, Fernanda Dias dos; Fantinel, Roberta Aparecida; Weiler, Elenice Broetto; Cruz, Jussara Cabral (Electronic Journal "Fórum Ambiental da Alta Paulista", 2020)
Soil loss through water erosion is one of the most serious problems in relation to productivity loss, whether agricultural or forestry. Knowing the environmental conditions of the area where the culture will be implanted is just as important as knowing the necessity of each culture for its development. That said, the present study aimed to analyze potential soil losses of forestall production at the Cachoeira Cinco Veados Watershed, RS, based on the Environmental Zoning of Silviculture for RS. The maps of potential soil losses are based on the Universal Soil Loss Equation (USLE), with the help of ArcGIS 10.5 Software, the maximum losses admitted were of 100 ton.ha-1.year-1. The areas of use with forest cover totalized 46,38 km² (4.638 ha), approximately 3% of the total area. According to the RS Forestry Zoning, the Cachoeira Cinco Veados Watershed, RS, comports the total of forestall area allowed (10,8%). The use of geotechonologies allowed to observe the analyzed variables.